2010
DOI: 10.1186/1472-6750-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor therapy with macroencapsulated endostatin producer cells

Abstract: BackgroundTheracyte is a polytetrafluoroethylene membrane macroencapsulation system designed to induce neovascularization at the tissue interface, protecting the cells from host's immune rejection, thereby circumventing the problem of limited half-life and variation in circulating levels. Endostatin is a potent inhibitor of angiogenesis and tumor growth. Continuous delivery of endostatin improves the efficacy and potency of the antitumoral therapy. The purpose of this study was to determine whether recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Endostatin has been studied in phase I and II clinical trials for patients with metastatic cancer and has shown low efficacy, however, a new more stable version of endostatin has re‐entered the clinic and is now used in certain countries for the treatment of lung and gastric cancer [94]. Recently, an immunoisolation device that contains endostatin‐expressing cells was used effectively for the treatment of melanoma and Ehrlich tumors in mice [98]. This suggests that the macroencapsulation of engineered cells that produce endostatin may be innovate therapeutic strategy for treatment of malignancies (Table 1).…”
Section: Extracellular Matrix Pgsmentioning
confidence: 99%
“…Endostatin has been studied in phase I and II clinical trials for patients with metastatic cancer and has shown low efficacy, however, a new more stable version of endostatin has re‐entered the clinic and is now used in certain countries for the treatment of lung and gastric cancer [94]. Recently, an immunoisolation device that contains endostatin‐expressing cells was used effectively for the treatment of melanoma and Ehrlich tumors in mice [98]. This suggests that the macroencapsulation of engineered cells that produce endostatin may be innovate therapeutic strategy for treatment of malignancies (Table 1).…”
Section: Extracellular Matrix Pgsmentioning
confidence: 99%
“…As of now, therapeutic approaches mediated by cells that mainly belong to the native and adaptive immune systems have been developed for treating cancers [589,590]. Cell therapy has achieved significant progress; however, challenges remain to demonstrate their clinical treatment efficacy and acceptable toxicity [591].…”
Section: Biomedical Polymers For Cell-mediated Cancer Therapymentioning
confidence: 99%
“…131 Recombinant fibroblasts expressing endostatin and encapsulated in PTFE capsules (Theracyte ™ ) suppressed melanoma in mice. 132 Melanomas were also suppressed when mouse myoblasts that were engineered to express angiostatin were encapsulated in alginate-PLL-alginate beads and grafted in tumor-bearing mice. 15 Combinatorial cell therapy has improved outcomes by attacking multiple targets.…”
Section: Applications and Clinical Trialsmentioning
confidence: 99%